Pengaruh Digital Leadership terhadap Kinerja Karyawan: Peran Mediasi kreativitas dan Perilaku Kerja Inovatif - Emma Yulianti; Nova Maharani (sekolah Tinggi Ilmu Ekonomi Dharma Putra Semarang, 2024)
The dynamic development of digitalization today increases the important role of digital leadership as a key factor to optimize employee performance. Research specifically through the development of creativity and innovative behavior in the workplace. This study aims to examine the indirect effect of digital leadership on performance through creativity and innovative work behavior of employees. The research was conducted at PT Semen Indonesia (Persero) Tbk. The research approach used is quantitative with survey research design where data is collected through questionnaires. The sampling technique used purposive sampling. This study involved 74 respondents who were analyzed using Smart PLS 4.0. The research findings explain that digital leadership does not directly affect the performance of PT Semen Indonesia (Persero) Tbk employees, but has an indirect influence through innovative work behavior. Meanwhile, creativity is not proven to mediate the effect of digital leadership on employee performance. Digital leadership is able to increase employee creativity, but employee creativity is not able to improve the performance of PT Semen Indonesia (Persero) Tbk employees. The research findings underscore the important role of digital leadership to drive employee performance. The results also imply that management can apply digital leadership as a strategy to increase creativity and innovative behavior in the workplace where innovative work behavior drives employee performance.